Stenografi sebagai Salah Satu Mata Pelajaran di Sekolah Menengah Kejuruan (SMK) Bisnis dan Manajemen - Bambang Suyono (Universitas Negeri Malang, 2016)
This research was designed to describe the learning-teaching in processes in Stenography as implemented by the Vocational Secondary Schools of Business and Management (SMK Bisnis dan Manajemen). The sample consisted of 14 teachers of Stenography taken purpossively from state and private SMK in Malang. Data were gathered by using an interview guide and observations, and analysed descriptively in persentage measures. It was concluded that in general the components of learning-teaching process in Stenography was good enough. Most pf Stenography teachers have had academic and professional qualification, applied adequate methods of teaching, selected assessment strategies properly, and involved all aspects of Stenography in evaluation processes.